KUASA ADAT BERTUMPU SYARA’: - Suleman, Zulfitri Zulkarnain (Institut Agama Islam Ngawi, 2023)
This article aims to critically examine the power of custom based on sharia' in the dynamics of the encounter between custom and Islamic law in Gorontalo. This research is aimed at showing how localities are involved in a very dynamic histo-sociological encounter or struggle between Islamic law and culture. This research uses literature study (library research) with a qualitative approach. This study found that the power of customs or traditions will never fade in Gorontalo society as a traditional region. Because customs or traditions are identity, so losing tradition is the same as losing identity. The local customs or culture of the Gorontalo people, which are preserved and practiced to this day, are the result of the dialectic between customary law and Islamic law. The power of this custom is stronger because it is based on the Shari'a, giving birth to the philosophy of “adati hula-hulaa to saraa, saraa hula-hulaa to syara'”. The meaning in the current context is actually to strengthen the power of custom so that there is no conflict in society that pits custom against Islamic law.